Strategi Marketing Pada CV. Kembar Jaya Kreatif Dengan Memanfaatkan Analisis Swot Serta QSPM - Tradiga Nur Aziz; Muhamad Rizal; Ria Arifianti; Asmaul Husna (Bahtera Inovasi, 2021)
CV. Kembar Jaya Kreatif is an industry engaged in garment or convection. The results of the CV. Kembar Jaya Kreatif from September 2017 to April 2019 can be seen if there are some months of income that do not meet the income target that has been set. Therefore CV. Kembar Jaya Kreatif is obliged to devise a new strategy in order to increase income in order to achieve the targets that have been set. SWOT analysis is used to obtain alternative strategies, where strategic alternatives are obtained from internal and external aspects of the industry. Information and research data consist of primary and secondary information, the analytical tools used in this research are the IFE (Internal Factor Evaluation) matrix, the EFE (External Factor Evaluation) matrix, the IE (Internal-External) matrix, the SWOT matrix (Strengths, Weakness). , Opportunities, and Threats), as well as QSPM (Quantitative Strategic Planning Matrix). The SWOT matrix creates 5 strategic alternatives that can be implemented by the industry. Based on the QSPM results from 5 alternatives, one of the prioritized alternative strategies is to use existing technology to carry out marketing activities and sell products online such as through social media and e-commerce with a TAS score of 6, 303.